1993
DOI: 10.1099/00221287-139-11-2635
|View full text |Cite
|
Sign up to set email alerts
|

Immunological specificity of oral Eubacterium species

Abstract: ~Antigens of Eubacterium species including E. alactolyticum, E. brachy, E. nodatum, E. saburreum, E. timidum, E. yurii subsp. yurii and E. yurii subsp. margavetiae, which have been isolated frequently from periodontal pockets and associated with periodontal diseases, were extracted by ultrasonication from whole bacterial cells. Antigens were also prepared from E. aerofaciens, E. lentum and E. rectale, which have been found in intestinal tracts and infected abscesses in human oral cavities. The antigens of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…We have found that the oral Eubacterium species are clearly distinguished by serological reactions (24), and this immunological heterogeneity suggests that they are a genetically heterogeneous group of microorganisms. There is no comprehensive study of relationships among Eubacterium species by DNA reassociation, although the limited data on the G + C content of DNA suggests heterogeneity and the need for research.…”
mentioning
confidence: 79%
“…We have found that the oral Eubacterium species are clearly distinguished by serological reactions (24), and this immunological heterogeneity suggests that they are a genetically heterogeneous group of microorganisms. There is no comprehensive study of relationships among Eubacterium species by DNA reassociation, although the limited data on the G + C content of DNA suggests heterogeneity and the need for research.…”
mentioning
confidence: 79%
“…Proteins were transferred from SDS-PAGE gels to a nitrocellulose membrane (pore size 0n45 µm ; Bio-Rad) by using the transfer buffer system described by Burnette (1981), in conjunction with the trans blot system (Marysol) at a constant current of 350 mA for 4 h with cooling. Membranes were processed with slight modification as described previously (Nakazawa & Hoshino, 1993). Briefly, a rabbit immune antiserum (1 : 1000) was used as first antibody, goat anti-rabbit IgG conjugated with peroxidase (1 : 1000) was used as the second antibody and the colour was then developed.…”
Section: Methodsmentioning
confidence: 99%
“…Because of its broad definition, the genus has historically acted as a repository for a large number of phenotypically diverse organisms (Cheeseman et al, 1996 ;Nakazawa & Hoshino, 1993). In addition to their phenotypic heterogeneity, it is reported that the bacterial species belonging to the genus are not phylogenetically homogeneous and several species may be closely related to members of the genus Clostridium (Collins et al, 1994 ;Willems et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…After electrophoresis, the gel was stained with Coomassie brilliant blue R-250 or used for Western transfer. Western transfer of the antigens from the gel to a nitrocellulose membrane was performed as described previously (19,34). An immunoblotting analysis was carried out by using goat anti-rabbit immunoglobulin G conjugated with peroxidase as the second antibody as described previously (19).…”
Section: Methodsmentioning
confidence: 99%
“…Western transfer of the antigens from the gel to a nitrocellulose membrane was performed as described previously (19,34). An immunoblotting analysis was carried out by using goat anti-rabbit immunoglobulin G conjugated with peroxidase as the second antibody as described previously (19). It has been reported that a polypeptide is a main antigen of strain G7201T (17).…”
Section: Methodsmentioning
confidence: 99%